Effects of cognitive behavioral therapy for patients with rheumatoid arthritis: a systematic review and meta-analysis. Issue 10 (25th November 2020) - Shen, Biyu; Li, Yongchang; Du, Xian; Chen, Haoyang; Xu, Yucheng; Li, Huiling; Xu, Guang-Yin
ABSTRACT: This study aimed to assess the effects of cognitive behavioral therapy on the psychological and physiological health of rheumatoid arthritis patients. An extensive literature search was conducted, using the PubMed, Web of Science, Cochrane Library, Embase, CNKI Scholar, WanFang, and VIP databases, from inception to December2018. The quality of the studies was evaluated by 2 independent authors, according to the basic criteria provided by the Cochrane Handbook for evaluating randomized trials. Meta-analysis was performed with Review Manager 5.3. Six randomized controlled trials met the inclusion criteria of the current study. Using standard mean differences (SMD) and 95% confidence intervals (CI), our results showed that cognitive behavioral therapy could significantly reduce levels of anxiety (SMD = −0.30, 95% CI [−0.52, −0.09], P= 0.005) and depression (SMD = −0.48, 95% CI [−0.70, −0.27], P< 0.00001), and relieve fatigue symptoms (SMD = −0.35, 95% CI [−0.60, −0.10], P= 0.006) in rheumatoid arthritis patients.This is the first known assessment of the efficacy of cognitive behavioral therapy on rheumatoid arthritis patients using meta-analysis. Large-scale randomized controlled trials need to be implemented to further explore this issue.